GC-MS analysis and antifungal activity from galls of Guiera senegalensis J.F Gmel (Combretaceae) - Pierre AED Sombié, Kiessoum Konate, Estelle Youl, Ahmed Y Coulibaly, Martin Kiendrébéogo, Muhammad I Choudhary, O G Nacoulma (Journal of Applied Pharmaceutical Science, 2013)
Guiera senegalensis is a well known medicinal plant which is used as a drug in Burkina Faso. The aim of this study was to investigate the chemical composition and antifungal activity from galls of Guiera senegalensis against different kinds of fungi in vitro. The chemical composition of the Guiera senegalensis volatile compounds obtained from the galls was analysed using gas chromatograph (GC)-flame ionization detectors (FID) and GC-MS. Thirteen (13) components were identified for hexane-acetone (50:50) column fraction of hydroacetone extract and twenty one (21) compounds for hexane-acetone (50:50) column fraction of aqueous decoction extract. This composition differed according to the kind of extract. The ethyl acetate fraction extract from hydroacetone extract (EAF/HAE) exhibited the highest of flavonol content (0.56 ± 0.01 mg QE/100 mg of fraction). The G. senegalensis exhibited an interesting antifungal activity against all strains tested.
Keywords: Galls, Guiera senegalensis, Volatile compounds, Flavonols content, Antifungal activity.